Factors influencing the implementation of business intelligence among small and medium enterprises in Lebanon - Kfouri, Georges; Skyrius, Rimvydas (Information & Media, 2017)
The goal of the study presented in this paper is to examine the factors that influence implementation of business intelligence (BI) among small and medium enterprises (SMEs) in Lebanon. A survey involved 56 managers from the SMEs selected for the research. Consequently, interviews and questionnaires based on the five point Likert scale were used to collect data for the primary research. A literature review has enabled selection of critical success factors identified by previous researchers. Content analysis of the survey data was used to classify the data on BI implementation factors using the three broad perspectives: organisational, processes, and technological perspective.
Keywords: SMEs; Business Intelligence; Critical Success factors